Auditoría interna y su efecto en el cumplimiento de los objetivos estratégicos de las PYMES comerciales - Varas Navas, Juan Gabriel (2020)
This research work entitled "INTERNAL AUDIT AND ITS EFFECT ON THE COMPLIANCE OF THE STRATEGIC OBJECTIVES OF COMMERCIAL SMEs.", Was carried out in order to obtain information related to companies in the commercial SME sector by virtue of being the main source production of goods and services, bases of the social development of the country. For this, it was carried out through the analysis of the case of one of the companies in that sector domiciled in the city of Guayaquil, Guayas province. The objective of the investigation was to design an audit model that allows the identification, evaluation and mitigation of risks, as well as the application of controls that allow the administration to make timely decisions………..